2014
DOI: 10.1038/labinvest.2014.51
|View full text |Cite
|
Sign up to set email alerts
|

Vitronectin-binding PAI-1 protects against the development of cardiac fibrosis through interaction with fibroblasts

Abstract: Plasminogen activator inhibitor-1 (PAI-1) promotes or abates fibrotic processes occurring in different organs. Binding of PAI-1 to vitronectin, an extracellular matrix component, may inhibit vitronectin–integrin complex-mediated cellular responses in pathophysiological conditions. To investigate the importance of plasmin suppression vs vitronectin-binding pathways of PAI-1 in cardiac fibrosis, we studied uninephrectomized mice fed a high salt diet and infused with angiotensin II (Ang II) together with differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 74 publications
(67 reference statements)
0
18
0
Order By: Relevance
“…To better realise the therapeutic potential of PAI-1 blockade, it is important to understand the relative contribution of these two pathways in each disease setting. Studies reported to define the contribution of vitronectin and/or protease binding roles of PAI-1 in fibrotic or angiogenic disease pathways have been limited to the administration of recombinant mutant PAI-1 molecules 4446 , which may be impacted by the presence of endogenous PAI-1 or challenges in administering PAI-1 at physiologically relevant levels to specific target cells or tissues. MEDI-579 is effective in a mouse model of diabetic kidney disease 47 – a model demonstrated to be dependent upon the protease-inhibitory activity of PAI-1 alone 48 .…”
Section: Discussionmentioning
confidence: 99%
“…To better realise the therapeutic potential of PAI-1 blockade, it is important to understand the relative contribution of these two pathways in each disease setting. Studies reported to define the contribution of vitronectin and/or protease binding roles of PAI-1 in fibrotic or angiogenic disease pathways have been limited to the administration of recombinant mutant PAI-1 molecules 4446 , which may be impacted by the presence of endogenous PAI-1 or challenges in administering PAI-1 at physiologically relevant levels to specific target cells or tissues. MEDI-579 is effective in a mouse model of diabetic kidney disease 47 – a model demonstrated to be dependent upon the protease-inhibitory activity of PAI-1 alone 48 .…”
Section: Discussionmentioning
confidence: 99%
“…The binding of PAI-1 to vitronectin blocks the vitronectin–integrin αVβ3 interaction, and regulates variety of cell activities including adhesion, migration, proliferation and survival. 58 Complex of PAI-1-vitronectin, may inhibit vitronectin–integrin complex, which mediates cellular responses in pathophysiological conditions like cardiac fibrosis, 58 but also in tumor progression thus promotion of angiogenesis in cancer tissue. 59 Data received by Lijnen et al showed that stable PAI-1 bounded to vitronectin was cleaved and inactivated by MMP-3, however, the cleaved protein did not bind to vitronectin.…”
Section: Stromelysinsmentioning
confidence: 99%
“…Moreover, it has been shown that during the plaque-induced inflammatory reaction, secreted cytokines induce the production of VN [ 41 ] that establishes interaction with coagulation and fibrinolysis-related proteins and binds to and stabilizes the plaque-induced plasminogen activator inhibitor-1 (PAI-1), a protein that suppresses the conversion of plasminogen to active plasmin [ 41 ]. The decomposition of the intra-arterial thrombus is suppressed by the action of the PAI-1/VN complex, which suggests that the decomposition of thrombus produced by the ruptured plaque would also be suppressed [ 46 , 47 ]. Additionally, VN can promote cell adhesion via the ανβ3 integrin in the cell membrane and ECM, which is hindered by PAI-1 to inhibit cell proliferation and induce apoptosis [ 46 , 48 ].…”
Section: Discussionmentioning
confidence: 99%